PENGARUH TEKNOLOGI INFORMASI, KEAHLIAN KOMPUTER, FORMALISASI PENGEMBANGAN SISTEM INFORMASI, DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP SISTEM INFORMASI AKUNTANSI (Studi Empiris pada Rumah Sakit Swasta yang Terdaftar di Dinas Kesehatan Kota Pekanbaru) - Syaradila R., Irma; Hasan, Amir; Elfi Ilham, Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the influence of information technology, computer expertise, formalization of information system development, and top management support on Accounting Information System (AIS). This research uses Private Hospitals in Pekanbaru as objects in 2017.The methods used in this research was multiple linear regression. The sampling methods used was total sampling which counted 16 private hospitals that listed in department of health in Pekanbaru and using information technology on implementation of the accounting process. For the unit of analysis in this research is financial staff, services staff, income staff, and purchases staff that using Accounting Information System (AIS) on Accounting process. So this research uses 64 people as the respondents. The results of the hypothesis test showed that information technology, computer expertise, formalization of information system development, and top management support have effect on Accounting Information System (AIS) with 0.000, 0.000, 0.026, 0.000 significance.Keywords : Information Technology, Computer Expertise, Formalization Of Information System Development, Top Management Support, Accounting Information System (AIS).